2021
DOI: 10.1155/2021/6663553
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Thyroid Homeostasis and Obesity in Subclinical Hypothyroidism: Community-Based Cross-Sectional Research

Abstract: Objective. It remains unknown whether obesity has an effect on the pituitary-thyroid feedback control axis in subclinical hypothyroidism (SCH). We aimed to investigate the association of thyroid homeostasis with obesity in a SCH population. Methods. Our study consisted of a community-based and cross-sectional study from the Epidemiological Survey of Thyroid Diseases in Fujian Province, China. A total of 193 subjects with SCH (90 males and 103 females) without a history of treatment of thyroid disease, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…However, contradictory findings were reported in others (17,35,36). Similar to our findings in pregnant women, several crosssectional studies among Chinese population reported that a decreased sensitivity/increased resistance to thyroid hormones were associated with reduced risk of pre-diabetes (17), lowered levels of HbA1c (35), or body mass index (BMI) (36). A crosssectional study (17) among Chinese adults reported that per SD increase in TSHI, TT4RI, and parametric TFQI and decrease in FT3/FT4 were associated with decreased risk of prediabetes by 9%-11%.…”
Section: Results Explanation and Potential Mechanisms Of Thyroid Resi...mentioning
confidence: 86%
See 2 more Smart Citations
“…However, contradictory findings were reported in others (17,35,36). Similar to our findings in pregnant women, several crosssectional studies among Chinese population reported that a decreased sensitivity/increased resistance to thyroid hormones were associated with reduced risk of pre-diabetes (17), lowered levels of HbA1c (35), or body mass index (BMI) (36). A crosssectional study (17) among Chinese adults reported that per SD increase in TSHI, TT4RI, and parametric TFQI and decrease in FT3/FT4 were associated with decreased risk of prediabetes by 9%-11%.…”
Section: Results Explanation and Potential Mechanisms Of Thyroid Resi...mentioning
confidence: 86%
“…Elevated indices of thyroid resistance has been observed to be associated with multiple unfavorable metabolic factors or disorders in general population including adipocyte fatty-acidbinding protein (34), obesity (15), type 2 diabetes, metabolic syndromes, or even diabetes-related mortality (14). However, contradictory findings were reported in others (17,35,36). Similar to our findings in pregnant women, several crosssectional studies among Chinese population reported that a decreased sensitivity/increased resistance to thyroid hormones were associated with reduced risk of pre-diabetes (17), lowered levels of HbA1c (35), or body mass index (BMI) (36).…”
Section: Results Explanation and Potential Mechanisms Of Thyroid Resi...mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that thyroid hormone resistance may be affected by fat accumulation. A previous study by Zhou et al found that obese patients had higher TSHI and TFQI levels compared to the control group, and TSHI and TFQI decreased significantly over time after bariatric surgery [ 41 ]. In addition, a cross-sectional analysis also showed that the secretory capacity of the thyroid gland (SPINA-GT) and TSHI were significantly negatively related to obesity indices, suggesting that obesity reduces levels of thyroid homeostasis indices [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reduced thyroid hormone sensitivity caused by impaired expression of Dio2 may connected with hypertension. Thirdly, diabetes and obesity, which are also risk factors for hypertension, have been reported to be associated with impaired sensitivity of thyroid hormones 17,36 . Although we have excluded participants with diabetes, adjusted multiple metabolic variables, and conducted subgroup analyses stratified by BMI levels, there was still possibility that metabolic disorders served as cross-talk between TFQI and blood pressure.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%